Physical phenomena in metal-organic frameworks: mechanical, vibrational, and dielectric response - Ryder, M (2017)
This thesis entails the utilisation of ab initio density functional theory (DFT) in conjunction with neutron and synchrotron spectroscopy to study the mechanical, vibrational, and dielectric response of metal-organic framework (MOF) materials at the molecular level. MOFs are crystalline materials with nanoscale porosity, which have garnered immense scientific and technological interest for a wide variety of innovative engineering applications. One part of the thesis involves using low-frequency lattice vibrations to characterise the various physical motions that are possible for framework materials. These collective modes detected at terahertz (THz) frequencies have been used to reveal a broad range of exciting possibilities. New evidence has been established to demonstrate that THz modes are intrinsically linked to anomalous elasticity underpinning gate-opening and pore-breathing mechanisms, and to shear-induced phase transitions and the onset of structural instability. The phenomenon of molecular rotor mechanisms and trampoline-like motions are also observed, along with the first experimental confirmation of coordinated shear dynamics. Additionally, a new method to characterise the effects of temperature, and hence thermally-induced structural amorphisation is reported. Finally, for the first time, the frequency-dependent (dynamic) dielectric response of MOF materials, across the extended infrared (IR) spectral region was reported. The results were obtained from experimental synchrotron radiation IR reflectivity and DFT to reveal the low-к dielectric response of MOFs and established structure-property trends that highlight them as promising systems for microelectronic device applications.